2011
DOI: 10.1177/1098300710366593
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Daily Living Skills to Seven Individuals With Severe Intellectual Disabilities: A Comparison of Video Prompting to Video Modeling

Abstract: We conducted a systematic replication of Cannella-Malone et al. by comparing the effects of video prompting to video modeling for teaching seven students with severe disabilities to do laundry and wash dishes. The video prompting and video modeling procedures were counterbalanced across tasks and participants and compared in an alternating treatments design within a multiple probe across participants design. For six participants, video prompting was more effective than video modeling, which was generally ineff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
116
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(119 citation statements)
references
References 15 publications
2
116
1
Order By: Relevance
“…The pattern continues for each step. Gardner and Wolfe (2013) reported that research investigating the comparative effects of the two interventions is limited (see Cannella-Malone et al, 2006;Cannella-Malone et al, 2011;Van Laarhoven & Van Laarhoven-Myers, 2006).…”
Section: Intervention Variations and Descriptionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The pattern continues for each step. Gardner and Wolfe (2013) reported that research investigating the comparative effects of the two interventions is limited (see Cannella-Malone et al, 2006;Cannella-Malone et al, 2011;Van Laarhoven & Van Laarhoven-Myers, 2006).…”
Section: Intervention Variations and Descriptionsmentioning
confidence: 99%
“…Authors of the remaining four studies compared the effects of VM to one or more interventions that differed from VM (Cannella-Malone et al, 2011;Mechling et al, 2014b;Murzynski & Bourret, 2007;Taber-Doughty et al, 2011). Cannella-Malone et al (2011 demonstrated one major exception to the generally positive effects of VM.…”
Section: Efficacy Of Vm: Visual Analysis and Pndmentioning
confidence: 99%
See 1 more Smart Citation
“…In the differentiation between video prompting and video modeling, Cannella-Malone et al (2011) established that students diagnosed with severe disabilities recorded greater success in the use of video prompts that in the use of video models. McKissick et al (2013) equally concluded that computer-aided instruction improves the rate in which the students achieve their literacy objectives.…”
Section: Fourth Research Questionmentioning
confidence: 99%
“…This systematic analysis involved two studies that applied technology in the provision of intervention to students with significant or severe disabilities (Cannella-Malone et al, 2011;McKissick et al, 2013). In the differentiation between video prompting and video modeling, Cannella-Malone et al (2011) established that students diagnosed with severe disabilities recorded greater success in the use of video prompts that in the use of video models.…”
Section: Fourth Research Questionmentioning
confidence: 99%